(untitled) (PANGEEA, 2025)
Heat waves frequency in southern Romania, between 1961 - 2013. Heat waves are a weather-complex phenomenon, which in recent years has obviously increased the nature of climate risk. This type of risk affects human activity and this requires a careful study of how to produce and emphasize the phenomenon. The large number of warm tropical air invasions is the main cause of exceeding the normal, average values, and this has led to numerous weather risky events which are frequently associated to heat waves.